Zero‐fluoroscopy transseptal puncture guided by right atrial electroanatomical mapping combined with intracardiac echocardiography: A single‐center experience. Issue 9 (7th June 2020) - Zhang, Guangping; Cheng, Liting; Liang, Zhuo; Zhang, Junmeng; Dong, Ruiqing; Hang, Fei; Wang, Xinlu; Wang, Ziyu; Zhao, Lin; Wang, Zefeng; Wu, Yongquan
Abstract: Background: Right atrial electroanatomical mapping may be combined with SoundStar 3D diagnostic ultrasound catheter (EAM‐ICE) as a zero‐fluoroscopy procedure for radiofrequency catheter ablation (RFCA). We aimed to evaluate the efficiency and safety of zero‐fluoroscopy transseptal puncture guided by EAM‐ICE and fluoroscopy combined with intracardiac echocardiography (F‐ICE) in patients with paroxysmal atrial fibrillation (PAF). Hypothesis: Zero‐fluoroscopy transseptal puncture is an effective and safe procedure. Methods: This study had a prospective design. A total of 57 patients with PAF were enrolled and assigned to two groups. Twenty‐seven patients were enrolled in the EAM‐ICE group, and 30 patients were enrolled in the F‐ICE group. Results: There were no statistically significant differences in baseline patient characteristics between groups. Transseptal puncture was successful in all patients (57/57, 100%). Total procedure time and duration of transseptal puncture were lower in the F‐ICE group (199.4 ± 26.0 minutes vs 150.7 ± 22.1 minutes, P = 0.000; 118.4 ± 19.7 vs 70.5 ± 13.5 minutes, P = 0.000). There was no use of fluoroscopy in the EAM‐ICE group (0 mGy vs 70.5 ± 13.5 mGy); the duration of fluoroscopy in the EAM‐ICE group was negligible (0 minutes vs 5.4 ± 1.9 minutes). No procedural complication occurred in either group. Conclusions: EAM‐ICE guided zero‐fluoroscopy transseptal puncture is an effective and safe procedure.